Pengaruh sanitasi terhadap tingkat kepuasan pasien dirumah sakit daerah Kabupaten Kuantan Singingi - Putri Permatasari; Ridwan Manda Putra; Agrina Agrina (SEHATI: Jurnal Kesehatan, 2021)
In hospital health care facilities, sanitation problems are the most important thing, the existence of problems such as clean water, sewage systems, conditions of garbage bins, sewerage systems and sanitation of building spaces cause discomfort for patients being treated. The inpatient room is part of the inpatient installation and is the most important part of the hospital. Therefore, this study aims to determine the effect of sanitation on the satisfaction level of inpatients at the General Hospital of Kuantan Singingi Regency. This research is a quantitative study using the spearmank rank analysis method. The research subjects were patients or their families who were waiting for the patient in the ward. The sample in this study amounted to 70 respondents, with the sampling technique incidental sampling. The analysis was carried out by using the Chi-Square test, the results showed that there was an influence between clean water sources, the P value = 16,556, the sewage system (X2), the P value = 16,170, the trash bin condition (X3), the P value = 16,640 variables. condition of sewerage (X4) obtained P value = 12,685 andÂ  sanitation of building space (X5) obtained P value = 17,637 level of patient satisfaction at the General Hospital of Kuantan Singingi Regency. The results concluded that there is an influence between all independent variables (sanitation) and the dependent variable (satisfaction). Based on the results of research on inpatient respondents at the Kuantan Singingi Hospital, namely the patient was satisfied and comfortable with the services provided. The satisfaction of these patients can improve the image and quality of the Kuantan Singingi Hospital to be good among the public and the government in Kuantan Singingi Regency.